Ischemic Stroke in Young Adults: Study of the Subtypes, Risk factors and Predictors of Poor Outcomes - Rajbhandari, Reema; Prajuli, Parmatma; Oli, K K (Nepal Journal of Neuroscience, 2019)
The aim of this study is to show the subtype, risk factors and predictors of poor outcomes in young ischemic stroke patients.Materials and Methods: It is a prospective study where only young onset ischemic stroke patients are analyzed.8% of total ischemic stroke sufferers were young adults; more prevalent in female (57.1%), with risk factors of smoking (47.6%) subtype cardio embolic (42.9%) was common. High NIHSS score was related to new event and correlation to mortality. Three month follow up showed MRS 2.86 ± 1.02. 57.1% of cases had significant disability (defined as MRS ≥ 3). There was a positive correlation of the cardio embolic subtype and the unclassified subtype to all three forms of poor outcomes, along with a positive correlation of the large artery atherothrombotic subtype to new events Recurrence of events (new stroke, sudden increase in symptoms and new TIAs) was observed in 14.3 %. Death was reported in 9.5% of cases.  Etiological diagnosis can be reached in majority of cases if an aggressive approach is maintained. This small scale study has provided an overview of the distribution of subtypes, risk factors and poor outcomes and their predictors. Cardiac diseases (esp. valvular disease) need to be taken more seriously to prevent cardio embolic strokes, while addressing other traditional risk factors to prevent the atherothrombotic subtypes.